2018
DOI: 10.1007/s00705-018-3833-7
|View full text |Cite
|
Sign up to set email alerts
|

Microevolution and independent incursions as main forces shaping H5 Hemagglutinin diversity during a H5N8/H5N5 highly pathogenic avian influenza outbreak in Czech Republic in 2017

Abstract: Here, we present a comprehensive analysis of the H5N8/H5N5 highly pathogenic avian influenza (HPAI) virus strains detected in the Czech Republic during an outbreak in 2017. Network analysis of the H5 Hemagglutinin (HA) from 99% of the outbreak localities suggested that the diversity of the Czech H5N8/H5N5 viruses was influenced by two basic forces: local microevolution and independent incursions. The geographical occurrence of the central node H5 HA sequences revealed three eco-regions, which apparently played… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…During the HPAI H5N8 clade 2.3.4.4 group B epizootic in 2016–2017, multiple reassortant variants of subtype H5N5 were detected in Europe [19,20,21,22,23,24,25,26]. However, the number of birds detected with HPAI H5N5 virus was limited compared to H5N8 [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the HPAI H5N8 clade 2.3.4.4 group B epizootic in 2016–2017, multiple reassortant variants of subtype H5N5 were detected in Europe [19,20,21,22,23,24,25,26]. However, the number of birds detected with HPAI H5N5 virus was limited compared to H5N8 [19].…”
Section: Introductionmentioning
confidence: 99%
“…After the first detection of HPAI H5N5 virus in the Kamchatka region of Russia in October 2016 [20], a total of 24 outbreaks were reported in 11 European countries [19,20,21,22,23,24,25,26], mainly affecting wild birds. Infections of poultry and captive birds were reported during eight outbreaks [23,24,25]. Genetic analysis suggested that different H5N5 variants were introduced into Europe [21,23,26].…”
Section: Introductionmentioning
confidence: 99%
“…HPAIV H5N8 detected in wild birds during August 2016 in Russia and an almost identical isolate reported in Poland shortly before the primary German outbreak at the beginning of November share over 99% identity throughout all segments with the concurring Ger‐11‐16 reassortant (Beerens et al., 2017; El‐Shesheny et al., 2017; Lee, Sharshov, et al., 2017; Marchenko et al., 2018, 2017; Poen et al., 2018; Pohlmann et al., 2017; Souvestre et al., 2019; Swieton & Smietanka, 2018). Further outbreaks with the equivalent Ger‐11‐16 reassortant were reported in, inter alia , Italy (Fusaro et al., 2017), the Netherlands (Beerens et al., 2017), Czech Republic (Nagy et al., 2018), Switzerland (Meier et al., 2017), France (Guinat et al., 2018) and Poland (Swieton & Smietanka, 2018).…”
Section: /2017: Reassortant Ger‐11–16—h5n8mentioning
confidence: 96%
“…While the Ger-12-16-N5.1 reassortant was identified in six European countries (the Netherlands, Poland, Italy, Croatia, Hungary and Germany; Fusaro et al, 2017;Nagy et al, 2018;Napp et al, 2018;Pohlmann et al, 2019;Swieton & Smietanka, 2018), only one further case with a virus genetically closely related to the Ger-12-16-N5.2 reassortant has been detected worldwide, in a wild goose in the Netherlands, May 2017 (A/Go/NL-Utrecht/17006881-001/2017, Table S2) (Bergervoet et al, 2019;Brown et al, 2017;Pohlmann et al, 2019). According to the genetic analysis, temporal course and geographic distribution, the poultry holding in Northern Germany infected with both HPAIV H5N5 reassortants is suggested as the most likely location of reassortment yielding Ger-12-16-N5.2.…”
Section: 016/2 017: Reassor T Ant G Er-12-16 -N5 -H5n5mentioning
confidence: 99%
See 1 more Smart Citation